2011
DOI: 10.1371/journal.pbio.1000622
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Nucleotide Substitutions and Insertion/Deletion Mutations Are Associated with Repeat Sequences

Abstract: The authors propose that short repeat sequences may play an important role in causing the pervasive clustering of mutations across diverse genomes from prokaryotes to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
105
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(127 citation statements)
references
References 39 publications
(58 reference statements)
20
105
0
Order By: Relevance
“…As observed previously (Tian et al 2008;McDonald et al 2011;Massouras et al 2012;Jovelin and Cutter 2013), we found a strong positive correlation between the genomic distribution of indels and SNPs. These correlated patterns of polymorphism are, in turn, correlated with local recombination, suggesting that the nonrandom distributions are due to hitchhiking and background selection (Begun and Aquadro 1992;Charlesworth et al 1993).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As observed previously (Tian et al 2008;McDonald et al 2011;Massouras et al 2012;Jovelin and Cutter 2013), we found a strong positive correlation between the genomic distribution of indels and SNPs. These correlated patterns of polymorphism are, in turn, correlated with local recombination, suggesting that the nonrandom distributions are due to hitchhiking and background selection (Begun and Aquadro 1992;Charlesworth et al 1993).…”
Section: Discussionsupporting
confidence: 90%
“…Several biological mechanisms have been proposed for the clustering of SNPs and indels, which appears to be ubiquitous in prokaryotes and eukaryotes (Tian et al 2008;Hodgkinson and Eyre-Walker 2011;McDonald et al 2011;Jovelin and Cutter 2013). Possibly indels (Tian et al 2008;Jovelin and Cutter 2013) and repeats (McDonald et al 2011) are mutagenic because they induce error-prone DNA polymerase replication near the indel or repeat (Yang and Woodgate 2007); the regions in which SNPs and indels occur are inherently mutagenic; or SNPs and indels are subject to the same population genomic processes.…”
Section: Nonrandom Distribution Of Snps and Indelsmentioning
confidence: 99%
“…Were this to be the case, we would expect that SVs with higher minor allele frequency (MAF) in the population would result in higher nucleotide diversity in their vicinity. However, in this study, we found that the nucleotide diversity was similar in the flanking regions of SVs with different MAFs ( Figure 2C), implying that SVs in cucumber might not be mutagenic agents, which is similar to a previous report (McDonald et al, 2011). It is worth noting that the higher nucleotide diversity in the vicinity of SVs might be caused to some extent by the potentially high rate of false SNP calls due to inaccurate read mapping near SVs.…”
Section: Mechanisms Of Sv Formationsupporting
confidence: 86%
“…Although the regional effect is also of great impor tance; that is, indels occur more frequently in the sites that are more susceptible to nucleotide substitutions (McDonald, 2011). Despite the prevalence of trans versions among the nucleotide substitutions, it should be noted that their distribution is almost unrelated to the presence of indels, and transversions accumulate primarily in the species that are morphologically more distant.…”
Section: Discussionmentioning
confidence: 99%